Influence of power converters on PV maximum power point tracking efficiency - Coelho, Roberto F.; dos Santos, Walbermark M.; Martins, Denizar C. (Eletrônica de Potência, 2014)
Maximum power point trackers (MPPT) are employed to maximize the photovoltaic modules output power, since it is strongly affected by changes on the incident solar radiation, surface temperature and load-type. Basically, a MPPT consists on a dc-dc converter (hardware) controlled by a tracking algorithm (software) and the combination of both, hardware and software, defines the tracking efficiency. This paper shows that even when the most accurate algorithm is employed, the maximum power point cannot be tracked, since its imposition as operating point depends on the dc- dc converter static feature and the load-type connected to its output. For validating the concept, the main dc-dc converters, i.e., Buck, Boost, Buck-Boost, Cuk, SEPIC and Zeta are analyzed considering two load-types: resistive and capacitive (regulated dc bus or battery). Simulation and experimental results are compared in order to confirm the theoretical analysis.